A comment on contemporary Sámi art - Sigrid Lien (The Open Arts Journal, 2014)
How do contemporary Sámi artists seek to establish new modes of historicity through photography? How do they speak about forgotten places and forgotten identities? This short commentary outlines the important contribution being made to current developments in photography-based contemporary art with a focus on Norway’s Sámi community. This text is published as a counterpart to the contribution to Disturbing Pasts from the artist Bente Geving.